Interactions between coral propagules in aquarium and field conditions - Poh Leong Loo (Nature Portfolio, 2020)
Abstract The effects of intraspecific and interspecific interactions between three species of scleractinian coral micro-colonies, namely Lithophyllon undulatum, Turbinaria mesenterina and Platygyra sinensis were evaluated for their survivorship, tissue loss and growth in both field (in-situ) and aquarium (ex-situ) conditions over 12 weeks. Regardless of environmental conditions and interactions, L. undulatum survived better (91.7 ± 6.2%) than T. mesenterina (75.0 ± 25.0%) and P. sinensis (60.4 ± 39.5%). Similarly, L. undulatum registered the lowest tissue loss (0.5 ± 0.7%) as compared to T. mesenterina (14.3 ± 19.4%) and P. sinensis (22.0 ± 30.0%). However, P. sinensis gained more weight (3.2 ± 5.2 g) than either T. mesenterina (2.7 ± 2.4 g) or L. undulatum (0.8 ± 1.1 g). In both environments, all three species in intraspecific interaction generally had higher survivorship, lower tissue loss and better growth than those in interspecific interaction except the latter in in-situ conditions had a twofold increase in growth (5.8 ± 3.7 g) than the former in-situ conditions (2.8 ± 3.7 g). Hence, all three species are potentially suitable for transplantation and mariculture except perhaps for P. sinensis which performed poorly in ex-situ conditions. Corals can be transplanted either with different colonies of the same species or together with other coral taxa. This study demonstrated that L. undulatum should be transplanted between T. mesenterina and P. sinensis for optimal growth and survival.